2020
DOI: 10.1002/ajim.23086
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk among career male and female Florida firefighters: Evidence from the Florida Firefighter Cancer Registry (1981‐2014)

Abstract: Background Firefighters are at increased risk for select cancers. However, many studies are limited by relatively small samples, with virtually no data on the cancer experience of female firefighters. This study examines cancer risk in over 100,000 career Florida firefighters including 5000 + females assessed over a 34‐year period. Methods Florida firefighter employment records (n = 109 009) were linked with Florida Cancer Data System registry data (1981‐2014; ~3.3 million records), identifying 3760 male and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 60 publications
2
60
0
Order By: Relevance
“…In 2018, our research team has conducted a linkage between records from FCDS and the Florida FMO that resulted in a dataset of 3928 male and female Florida career firefighters with cancer. Using this linked dataset we identified an increased risk of melanoma, prostate, testicular, thyroid, and late‐stage colon cancer among male firefighters, and brain and thyroid cancer among female firefighters 9 . These findings are fairly consistent with the most recently published meta‐analysis, although the magnitude of the estimates varied by cancer site 7 .…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…In 2018, our research team has conducted a linkage between records from FCDS and the Florida FMO that resulted in a dataset of 3928 male and female Florida career firefighters with cancer. Using this linked dataset we identified an increased risk of melanoma, prostate, testicular, thyroid, and late‐stage colon cancer among male firefighters, and brain and thyroid cancer among female firefighters 9 . These findings are fairly consistent with the most recently published meta‐analysis, although the magnitude of the estimates varied by cancer site 7 .…”
Section: Introductionsupporting
confidence: 84%
“…The details of the FCDS–FMO data linkage have been reported previously 9 . Briefly, FCDS performed a probabilistic linkage between 1981 and 2014 FCDS data (~3.3 million records) and 1972–2012 Florida State FMO employment and certification data ( n = 109,009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural fires fueled by common household furnishings can produce hundreds of compounds including those that may expose firefighters to vapor, gas, and particulate contamination (Austin et al 2001a(Austin et al , 2001bJankovic et al 1991). Epidemiological studies suggest that firefighters have increased risk for numerous types of cancer including testicular, prostate, and non-Hodgkin's lymphoma (Daniels et al 2014(Daniels et al , 2015Glass et al 2014; International Agency for Research on Cancer [IARC] 2010; Jalilian et al 2019;Lee et al 2020;LeMasters et al 2006;Pukkala et al 2009;Tsai et al 2015). As the fire service has become more aware of the fireground risks, personal protective equipment (PPE) manufacturers have developed new designs for turnout jacket and pants, hoods, gloves, and other aspects of the firefighting PPE ensemble.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted October 7, 2020. ; https://doi.org/10.1101/2020.10.06.20207498 doi: medRxiv preprint compared to the general Florida population (Ma et al 2006) and a more recent study of Florida firefighters using that state's cancer registry found that women firefighters had elevated risk of melanoma, thyroid, and brain cancer (Lee et al 2020).…”
Section: Introductionmentioning
confidence: 99%